As relações entre prosa e poesia e a busca pela comunicabilidade no projeto literário de Carlos Drummond de Andrade - Erthal, Claudia (2014)
In this present work we analyze some everyday chronicles inserted in the book Caminhos de João Brandão by Carlos Drummond de Andrade, considering aspects already present in his poetic production and the critical considerations presented in his essayistic chronicles. We present the hypothesis about the relationship between essay, chronic and poetry, not only because they are produced by the same writer, but by the specific characteristics of each gender. Furthermore, we consider that in this specific case of Drummond the everyday chronic would be a continuation to a literary project started in his poetic phase, the search for communicability by the expressive literary way adapted to the contingencies of everyday lives of modern readers. Initially, in order to seek an explicative way and presenting the specific characteristics of chronic, which allows us to relate it to other literary and daily genres, we trace its historical development, why the chronic arose and how it adapted to the Brazilian literary context. In the second phase, to understand the situation of poetry in the historical context of crisis (social, communicative, literary), we seek some critical considerations about the poetry of modernism, the Western and specifically on the social context of Drummond poetry, particularly the postwar context. We add also criticizes of Drummond in his own essays about the general situation of literature and his poetry present in Confissões de Minas and Passeios na ilha. In the last chapter, we analyze some chronicles and chronicpoems of the proposed book, seeking to prove our hypotheses and observe specific aspects present in the texts, which highlight the ironic discursive articulation and use of humor as strategies to enable the participation of the reader in the chronicles.